Flavor difference between freshly extracted sweetened kalamansi juice and frozen kalamansi syrup - Tinsay, Emma B.
The identification of difference in tasks between two kalamansi drinks---one from sweetened freshly extracted juice and an identical one from frozen kalamansi syrup was done with the use of a triangle test. Results were analyzed statistically and the findings expressed in terms of probability levels or by chance alone. Triangle test results revealed a significant difference in taste between the samples at 5% probability level. Objective analysis in terms of soluble solids content and % titratable acidity was done for both samples. Furthermore, a follow-up of the changes in these constituents in the frozen syrup, during a week of frozen storage, revealed no apparent significant change in the soluble solids content at 43.0%. Whereas, a decreasing % titratable acidity, expressed as anhydrous citric acid was observed from 2.95 to 2.73%.